The QSPR-THESAURUS: The Online Platform of the CADASTER Project. Issue 1 (March 2014) - Brandmaier, Stefan; Peijnenburg, Willie; Durjava, Mojca K.; Kolar, Boris; Gramatica, Paola; Papa, Ester; Bhhatarai, Barun; Kovarich, Simona; Cassani, Stefano; Roy, Partha Pratim; Rahmberg, Magnus; Öberg, Tomas; et al.
The aim of the CADASTER project (CA se Studies on theD evelopment andA pplication of inS ilico T echniques forE nvironmental Hazard andR isk Assessment) was to exemplify REACH-related hazard assessments for four classes of chemical compound, namely, polybrominated diphenylethers, per and polyfluorinated compounds, (benzo)triazoles, and musks and fragrances. The QSPR-THESAURUS website (http://qspr-thesaurus.eu ) was established as the project's online platform to upload, store, apply, and also create, models within the project. We overview the main features of the website, such as model upload, experimental design and hazard assessment to support risk assessment, and integration with other web tools, all of which are essential parts of the QSPR-THESAURUS.